2008
DOI: 10.1002/jmri.21542
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and spectroscopy for monitoring liver steatosis

Abstract: Purpose:To compare noninvasive MRI and magnetic resonance spectroscopy (MRS) methods with liver biopsy to quantify liver fat content. Materials and Methods:Quantification of liver fat was compared by liver biopsy, proton MRS, and MRI using inphase/out-of-phase (IP/OP) and plus/minus fat saturation (ϮFS) techniques. The reproducibility of each MR measure was also determined. An additional group of overweight patients with steatosis underwent hepatic MRI and MRS before and after a six-month weight-loss program. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(148 citation statements)
references
References 30 publications
2
143
0
3
Order By: Relevance
“…Th e results from these studies using a variety of interventions, either by diet alone ( 81,83,84,89,92,93 ) or in combination with diff erent exercise prescriptions ( 82,85 -88,92,94 ), have consistently reported a signifi cant reduction in liver fat by an average of ~ 40 % (ranging from 20 to 81 % ). Th e degree of hepatic fat reduction was proportional to the intensity of the lifestyle intervention and generally required a body weight loss between ~ 5 and 10 % ( 82,88,92 ).…”
Section: Lifestyle Interventionmentioning
confidence: 99%
“…Th e results from these studies using a variety of interventions, either by diet alone ( 81,83,84,89,92,93 ) or in combination with diff erent exercise prescriptions ( 82,85 -88,92,94 ), have consistently reported a signifi cant reduction in liver fat by an average of ~ 40 % (ranging from 20 to 81 % ). Th e degree of hepatic fat reduction was proportional to the intensity of the lifestyle intervention and generally required a body weight loss between ~ 5 and 10 % ( 82,88,92 ).…”
Section: Lifestyle Interventionmentioning
confidence: 99%
“…The results from these studies using a variety of interventions, either by diet alone 81,83,84,89,92,93 or in combination with different exercise prescriptions, 82,[85][86][87][88]92,94 have consistently reported a significant reduction in liver fat by an average of $40% (ranging from 20% to 81%). The degree of hepatic fat reduction was proportional to the intensity of the lifestyle intervention and generally required a body weight loss between $5 to 10%.…”
Section: Lifestyle Interventionmentioning
confidence: 99%
“…Generally, the sensitivity and specificity of MRI for the detection of moderate and severe steatosis are greater than 80 and 95%, respectively; in addition, MRI has agreater than 85% sensitivity and a nearly 100% specificity for mild steatosis (intrahepatic fat 5±10%) (Mazhar et al 2009). It was confirmed by many studies which have reported very good correlations between quantitative estimations of hepatic steatosis on MRI compared with liver biopsy (Cowin et al 2008). Nevertheless this technique is very expensive, not always available in hospital and does not quantify fibrosis.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 71%